Preliminary study on the variation of radon-222 inside greenhouse of Shouguang county, China. (March 2016) - Li, Xiaohong; Xu, Xianqin; Li, Wanwei; Wang, Fei; Hai, Chunxu
Abstract: Studies on radon have become the focus of indoor radiation. In this study, we chose greenhouse to be the study field, the research aims to: (1) explore the diurnal variation of radon concentration inside greenhouse in Shouguang county, China; (2) pre-analyze the relationship between radon concentration, temperature and relative humidity, and shed light on the radon behavior characteristic inside greenhouse; (3) verify the feasibility of calculating radon radiation dose by using short-period detected radon concentrations in typical months in Shouguang county. The following conclusions were drawn. Firstly, the average radon levels in typical months in Shouguang county are all much higher than that in ordinary dwellings in China, diurnal and seasonal variations in radon levels are observed inside greenhouse. Secondly, temperature and relative humidity may play a role indirectly through affecting soil moisture and other factors. The mechanism need to be further studied. Thirdly, radon concentrations detected in typical months are still useful in preliminary estimation of radon radiation dose for vegetable-plant farmers in Shouguang county. Highlights: Diurnal and seasonal variations of radon in greenhouse were observed. Temperature and relative humidity may play a role in radon migration process in greenhouse. Radon levels detected in typical months are useful for preliminary radon radiation dose estimation.